The use of Functional Communication Training in reducing problem behaviors in children with autism - Arsic, Bojana B.; Gajic, Anja M. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2024)
The presence of behavioral problems correlates with communication deficits in people with autism spectrum disorder (ASD), and if a person with ASD is taught functional communication, which has the same purpose for them as the manifestation of behavioral problems, there can be a reduction, and for this, the procedure called functional communication training (FCT) is most often used. This paper aims to determine the effectiveness of the application of FCT for each of the behavioral functions, as well as how FCT can be implemented for each function, by reviewing the literature. The papers were searched using the Google Scholar and ProQuest search engines, and the literature review included those papers in which FCT was applied to reduce various behavioral problems. By reviewing the literature, it can be seen that FCT can be implemented with respondents who have different diagnoses, as well as different degrees of functionality in the way they communicate. In addition, FCT can be successfully implemented with participants exhibiting behavioral problems in various functions. Bearing in mind that FCT looks different for each of the mentioned functions, the importance of determining the behavioral function is emphasized, since it is a necessary prerequisite for the successful implementation of FCT. In addition, bearing in mind the effectiveness of the application of FCT in reducing behavioral problems exhibited by children with ASD, it is emphasized that it is necessary to conduct training for special education teachers and parents, as well as all others who work with this population on the application of FCT.
Keywords: autism; functional communication training; treatment; problem behaviors